Periodontal disease and chronic kidney disease: mechanistic insights and novel therapeutic perspectives - Li, Shuxin; Cao, Hongliang; Zhang, Yueqiu; Wang, Fulin; Huang, Gengchen; Wang, Binbin; Wei, Wei; Wang, Gang (Frontiers in Cellular and Infection Microbiology, 2025)
Periodontal disease (PD) is one of the most common chronic diseases of the oral cavity, and it usually refers to chronic inflammatory diseases caused by the infection of pathogenic microorganisms in the oral cavity. PD mainly affects the tissues around the teeth, causing inflammation of the gums and periodontium, destroying the alveolar bone, and even leading to tooth loosening. Many studies have shown that PD is not only limited to oral health but is also associated with diseases of multiple systems throughout the body. In recent years, more and more studies have focused on the interaction between PD and urologic diseases, especially chronic kidney disease (CKD). PD is also a typical oral disease frequently observed in patients with kidney disease. This paper reviews the potential link between PD and CKD and discusses the interaction’s pathologic mechanisms and clinical implications. In addition, this review aims to identify possible pathogenic mechanisms and suggest potential ways to target PD to prevent and treat CKD. This would lead to better treatment options to delay the progression of CKD.